2017
DOI: 10.3102/0002831217724116
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Income Segregation in Schools: The Role of School Attendance Zone Geography

Abstract: This study investigates how much the geographic shapes of school attendance zones contributes to their levels of income segregation while holding constant levels of income segregation across residential areas. Income segregation across attendance zones is measured with the rank ordered information theory index. Income segregation across residential areas is measured using a spatial variant of segregation (newly developed to predict income segregation in school attendance zones). Findings indicate income segreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 33 publications
0
15
0
2
Order By: Relevance
“…Similarly, Saporito (2017) found evidence that irregularly shaped districts—again, which are often associated with gerrymandering—do not necessarily contribute to increased levels of economic segregation. From his analysis of 2009–2010 SABINS data, Saporito (2017) learned just the opposite. He summarized,I find that on average, school districts with irregularly shaped attendance zones have lower levels of income segregation, net of income segregation within districts’ residential areas.…”
Section: Primary Research Themes In Gis Education Researchmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, Saporito (2017) found evidence that irregularly shaped districts—again, which are often associated with gerrymandering—do not necessarily contribute to increased levels of economic segregation. From his analysis of 2009–2010 SABINS data, Saporito (2017) learned just the opposite. He summarized,I find that on average, school districts with irregularly shaped attendance zones have lower levels of income segregation, net of income segregation within districts’ residential areas.…”
Section: Primary Research Themes In Gis Education Researchmentioning
confidence: 96%
“…In contrast, although relatively rare, irregularly shaped districts tended most always to be racially diverse, which, according to them, is contradictory to many other claims that oddly shaped districts reflect historical gerrymandering for the purposes of exclusion. Similarly, Saporito (2017) found evidence that irregularly shaped districtsagain, which are often associated with gerrymandering-do not necessarily contribute to increased levels of economic segregation. From his analysis of 2009-2010 SABINS data, Saporito (2017) learned just the opposite.…”
Section: Gerrymanderingmentioning
confidence: 97%
See 1 more Smart Citation
“…In some of this work, researchers found that irregularly shaped attendance zones exacerbate racial segregation (Richards, 2014(Richards, , 2017Richards & Stroub, 2015). Other scholars examined the same geospatial data sets and found that irregularly shaped boundaries alleviate racial and income segregation in schools (Saporito, 2017;Saporito & Van Riper, 2016).…”
Section: Refining the Quantitative Geospatial Techniques Applied By Rmentioning
confidence: 99%
“…Entre estos elementos encontramos la segregación residencial por origen socioeconómico (ver por ejemplo, Bonal, Zancajo y Scandurra, 2019;Boterman, 2019;Owens, 2018;Owens, Reardon y Jencks, 2016), las preferencias heterogéneas de las familias (Oosterbeek, Sóvágó y van der Klaauw, 2019), una oferta diferenciada como la expansión de los centros educativos de titularidad concertada en España (Fernández Enguita, 2008;Murilllo y Martínez-Garrido, 2017;Murillo, Belavi y Pinilla, 2018; Save the Children, 2019a), el sistema de asignación de los estudiantes en los centros a partir las preferencias de las familias (Calsamiglia, Martínez-Mora y Miralles, 2017), u otros mecanismos de la política educativa (Gortázar, Mayor y REICE. Revista Iberoamericana sobre Calidad, Eficacia y Cambio en Educación 221 Montalbán, 2020;Saporito, 2017). Muchos de estos elementos mencionados que recoge la literatura son comunes a las distintas comunidades autónomas de España, salvo aquellos factores socioeconómicos de cada comunidad autónoma (como la segregación residencial) y las políticas educativas de competencia autonómica o municipal.…”
Section: Introductionunclassified